PEMBELAJARAN BLENDED LEARNING MENGGUNAKAN GOOGLE CLASROOM DI PERGURUAN TINGGI - Ferdinanda Sherly Noya; Denissa Alfiany Luhulima (INSTITUTIO : JURNAL PENDIDIKAN AGAMA KRISTEN, 2021)
Age 17-19 years is the age of children who are at the college level. In this day and age, they are classified as generation Z children or often referred to as digital natives. Digital natives children are 'opportunistic' and 'omnivorous' people who enjoy things in an online environment (want to get information quickly); likes collaboration from one person to another (networked), and multitask. In the learning process, especially in higher education, this also needs to be considered, in order to help the teaching and learning process run well. Blended Learning is a learning model that combines conventional learning processes and online or network-based learning processes. Students can learn online without also putting aside conventional learning, which in the end these two processes can complement each other. Google Classroom is a system created by Google to assist in the online learning process. The convenience of google classroom which can be accessed via a computer or mobile phone can facilitate teachers and students in the online learning process, for that the purpose of scientific writing is to describe the blended learning process and blended learning using google classroom in universities. The use of google classroom as a system that can support the blended learning process, can make it easier for students to carry out the learning process online or online, and also make it easier for teachers to provide learning even though not in class.Keywords: Blended Learning, Google Classroom, University.Â